We have changed our privacy policy. In addition, we use cookies on our website for various purposes. By continuing on our website, you consent to our use of cookies. You can learn about our practices by reading our privacy policy.
© 2016 Shmoop University, Inc. All rights reserved.

Cramer's Rule Examples

Example 1

Use Cramer's Rule to find Dx, Dy, x, and y in the following system of equations.

3x – 4y = 8
2x + 2y = 6

Example 2

Use Cramer's Rule to find Dx, Dy, x, and y in the following system of equations.

-2x + 3y = 7
4x – 3y = 6

Example 3

Use Cramer's Rule to find Dx, Dy, x, and y in the following system of equations.

2x + y = 4
4x + 2y = 6

People who Shmooped this also Shmooped...